2011
DOI: 10.1177/155005941104200309
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cognitive Functions and Nitric Oxide Levels in Patients with Dementia

Abstract: Dementia is defined as a clinical syndrome characterized by acquired loss of cognitive and emotional abilities, severe enough to interfere with daily functioning and quality of life. Event related potentials (ERP) are sensitive to task variables that relate to cognitive behavior. They might be altered in patients with disorders of cognition such as dementia. Application of the P300 ERP component to the study of cognitive disorders provides a means of quantifying the level of mental impairment. At high levels, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Liu et al [25] suggested that generation of reactive nitrogen species (RNS) and ROS triggers oxidative stress and eventually leads to neuronal damage. Thus, the increased free radical generation may ultimately lead to synaptic dysfunction which is an important pathophysiological component of AD [26]. Moreover, Kamat et al [10] also suggest that oxidative stress causes cognitive deficiency, neurofibrillary tangle (NFT)-like pathological changes, and oxidative stress as seen in AD pathology via tau hyperphosphorylation.…”
Section: Nmda Receptor-mediated Oxidative Stressmentioning
confidence: 99%
“…Liu et al [25] suggested that generation of reactive nitrogen species (RNS) and ROS triggers oxidative stress and eventually leads to neuronal damage. Thus, the increased free radical generation may ultimately lead to synaptic dysfunction which is an important pathophysiological component of AD [26]. Moreover, Kamat et al [10] also suggest that oxidative stress causes cognitive deficiency, neurofibrillary tangle (NFT)-like pathological changes, and oxidative stress as seen in AD pathology via tau hyperphosphorylation.…”
Section: Nmda Receptor-mediated Oxidative Stressmentioning
confidence: 99%
“…We find an increase in serum nitric oxide in the MCI patients and a decrease in AD. This is probably the consequence of the increased iNOS expression that we observe in the MCI patients, interestingly patients with AD show lower serum concentrations of NO [30] [31] [33] [34], which are not secondary to a decrease or disappearance of iNOS. It is possible that the lack of arginine that has been reported in AD patients [35] is the cause of such a decrease.…”
Section: Discussionmentioning
confidence: 76%